Reversible-deactivation radical polymerization (Controlled/living radical polymerization): From discovery to materials design and applications. (December 2020) - Corrigan, Nathaniel; Jung, Kenward; Moad, Graeme; Hawker, Craig J.; Matyjaszewski, Krzysztof; Boyer, Cyrille
Abstract: Reversible-deactivation radical polymerization (RDRP) processes, such as atom transfer radical polymerization (ATRP), reversible addition-fragmentation chain transfer (RAFT) polymerization and nitroxide mediated polymerization (NMP) have revolutionized polymer synthesis by providing polymer chemists with powerful tools that enable control over architecture, composition and chain length distributions. The user-friendly nature of these procedures have allowed RDRP-derived polymers to be used in the construction of advanced materials with unique and enhanced properties. This review covers the progress of RDRP from its conception to the current state-of-the-art. A brief introduction to the sources of RDRP, general mechanisms, and methodological progressions are presented, and the suite of advanced and highly tailorable materials possible through these techniques is discussed to illustrate the significant potential for even greater impact across multiple disciplines. Graphical abstract: Image, graphical abstract